Artificial Wombs and Abortion Rights - Cohen, I. Glenn (The Hastings Center report, 2017)
In a study published in late April in Nature Communications, the authors were able to sustain 105- to 115-day-old premature lamb fetuses—whose level of development was comparable to that of a twenty-three-week-old human fetus—for four weeks in an artificial womb, enabling the lambs to develop in a way that paralleled age-matched controls. The oldest lamb of the set, more than a year old at the time the paper came out, appeared completely normal. This kind of research brings us one step closer to providing excellent quality of life for premature newborns, but it also portends major legal and ethical questions, especially for abortion rights in America.